Is Graphitic Silicon Carbide (Silagraphene) Stable? - Yaghoubi, Alireza; Masenelli-Varlot, Karine; Boisron, Olivier; Ramesh, Singh; Melinon, Patrice (American Chemical Society, 2018)
Graphene is considered to be the most likely candidate for the postsilicon era; however, the problem with its zero band gap is challenging to overcome. A close relative of silicon, silicon carbide is expected to have a stable 2D polymorph which happens to be a wide-gap semiconductor. Unfortunately, the so-called silagraphene has proven to be elusive. To date, neither theoretical nor experimental studies have been conclusive. Here, we employ computational methods to determine the stable arrangements of silagraphene and establish their accurate band structure. We also experimentally validate our models by preparing and characterizing a number of graphitic features. Silagraphene exhibits a wide spectrum of optoelectronic properties (360-690 nm) as well as an unusual band structure with highly anisotropic transport properties, which originates from its nondispersive band near its K-point. This feature makes direct-indirect gap crossover extremely sensitive to ambient conditions, making silagraphene suitable for a range of sensors.